The effect of particle size, morphology and C-rates on 3D structured Co3O4 inverse opal conversion mode anode materials. (13th February 2017) - McNulty, David; Geaney, Hugh; Carroll, Elaine; Garvey, Shane; Lonergan, Alex; O'Dwyer, Colm
Abstract: Engineering Co3 O4 nanoparticles into highly ordered, 3D inverse opal (IO) structures is shown to significantly improve their performance as more efficient conversion mode Li-ion anode materials. By comparison with Co3 O4 microparticles, the advantages of the porous anode architecture are clearly shown. The inverse opal material markedly enhances specific capacity and capacity retention. The impact of various C rates on the rate of the initial charge demonstrates that higher rate charging (10 C) was much less destructive to the inverse opal structure than charging at a slow rate (0.1 C). Slower C rates that affect the IO structure resulted in higher specific capacities (more Li2 O) as well as improved capacity retention. The IO structures cycle as CoO, which improves Coulombic efficiency and limits volumetric changes, allowing rate changes more efficiently. This work demonstrates how 3D IOs improve conversion mode anode material performance in the absence of additive or binders, thus enhancing mass transport of Li2 O charge–discharge product through the open structure. This effect mitigates clogging by structural changes at slow rates (high capacity) and is beneficial to the overall electrochemical performance.